Using a Mock Trial Method to Enhance Effectiveness of Teaching Evidence-Based Practice in Nursing. Issue 6 (November 2015) - White, Cindy T.
Abstract : Traditional teaching methodologies may deter adult learning because of passive the exchange of knowledge. Teaching to the "evidence" substantiating best practice requires a systematic approach to transfer knowledge into clinical inquiry. A mock trial simulated role-play activity was selected to show the value of learning through active engagement. The nurse "defendant" was challenged to substantiate practice based on the evidence. Seminar participants (the jury) scrutinized testimony through deliberation before delivering the final verdict.